Organizations and their consumers: Bridging work and consumption. (September 2015) - Gabriel, Yiannis; Korczynski, Marek; Rieder, Kerstin
The last 20 years or so have seen a far-reaching reconfiguration of the characters that dominate the world of organizations. For much of its life, the study of organizations was dominated by two central characters, the manager and the worker, whose relationship with all its tensions, conflicts and accommodations unfolded with within a broader environment of markets, governments, shareholders, social institutions, technological forces and so forth. In recent years, however, there has been a substantial movement to change the two-actor show into a three-actor show, the organizational dyad into a triad. The newcomer to the stage has been the consumer, a character whose whims, habits, desires and practices are no longer seen as 'impacting on' the activities of managers and workers from the outside, but increasingly as defining them. This introduction to the Special Issue on 'Organizations and their Consumers' examines the ramifications of the rise of the consumer and the hegemony of global markets for (1) the nature of organizations and their management, (2) the employees and the labour process and (3) the consumers themselves as they increasingly find themselves doing work, usually unpaid, on behalf of organizations.